D-dimer: Preanalytical, analytical, postanalytical variables, and clinical applications. (17th November 2018) - Favresse, Julien; Lippi, Giuseppe; Roy, Pierre-Marie; Chatelain, Bernard; Jacqmin, Hugues; ten Cate, Hugo; Mullier, François
Abstract: D-dimer is a soluble fibrin degradation product deriving from the plasmin-mediated degradation of cross-linked fibrin. D-dimer can hence be considered a biomarker of activation of coagulation and fibrinolysis, and it is routinely used for ruling out venous thromboembolism (VTE). D-dimer is increasingly used to assess the risk of VTE recurrence and to help define the optimal duration of anticoagulation treatment in patients with VTE, for diagnosing disseminated intravascular coagulation, and for screening medical patients at increased risk of VTE. This review is aimed at (1) revising the definition of D-dimer; (2) discussing preanalytical variables affecting the measurement of D-dimer; (3) reviewing and comparing assay performance and some postanalytical variables (e.g. different units and age-adjusted cutoffs); and (4) discussing the use of D-dimer measurement across different clinical settings.